Peningkatan Hasil Belajar Simetri dengan Pendekatan CTL di Kelas V Sekolah Dasar - Yunita, Vilda; Ahmad, Syafri; Lena, Mai Sri (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
Abstract                The purpose of this study was to describe the improvement of learning outcomes of symmetry using the Contextual Teaching and Learning (CTL) approach at grade five-A of SDN 06 Padang Besi, Padang City. The subjects of this study were teacher and 23 students. The type of the research used was classroom action research using qualitative and quantitative approaches. This research was conducted in two cycles. The results showed: a) lesson plans in cycle 1 was 83,9% and increased to 94.6% in cycle 2, b) aspects of teacher in cycle 1 that is 83,7% and increased to 95% in cycle 2, c) aspects of students in cycle I, 82,5%, increased to 93,8% in cycle 2, d) the average of students’ learning outcomes in cycle 1 was 73,4 and increased to 87,1 in cycle 2. It could be concluded that the CTL approach can improve symmetry learning outcomes at grade five-A SDN 06 Padang Besi Padang City.  Keywords: Symmetry, CTL approach